The Implementation of Differentiated Instruction Integrated With Technology in English Class - Astawa, Made Candrika Widya; Krisna, Putu Adi; Agustini, Dewa Ayu Eka (IJLHE: International Journal of Language, Humanities, and Education, 2025)
The implementation of differentiated instruction is the focus of the Merdeka Curriculum in Indonesia, especially when integrated with technology. The aim is to adapt education to the needs, abilities, and interests of each student. This study explores how English teachers at SMK Negeri 3 Denpasar implement differentiated instruction integrated with technology in the classroom and how this affects students' beliefs in learning English. The method approach used in this study is a mixed-method approach, where qualitative data were collected through classroom observations, while quantitative data were collected through student questionnaires adapted from Horwitz's BALLI framework. The observation results showed that teachers differentiated content, process, and product based on student profiles and learning contexts. As a support for various learning strategies, this study integrated technological tools such as WhatsApp, Google Translate, Quizizz, and Canva. The questionnaire results showed that students had very high beliefs in their language learning abilities when faced with differentiated instruction supported by technology. These findings indicate that the learning model increased students' motivation and self-perception in learning English. This study highlights the importance of teacher adaptability and strategic use of technology to foster a student-centered learning environment that is aligned with the principles of the Merdeka Curriculum.